Analysis study and experiments SEM-EDS of particles and porosity of empty fruit bunches - Erdiwansyah, .; Asri, Gani; Desvita, Hera; Mahidin, .; Viena, Vera; Rizalman, Mamat; Sardjono, Ratnaningsih Eko
Palm oil biomass waste has a high energy value and can be converted into fuel. However, the high ash content from burning biomass waste is undesirable. This research aims to analyze the porosity values and length of particles from empty-fruit-bunches biomass samples different treatments. Analysis of the porosity and particle length of empty fruit bunches is the latest in this research. The analysis results show that the R-Square value with the regression model for each sample is (raw 0.88375, flowrate 1L/sec 0.99997, and temperature 30 ◦C 0.99996). Meanwhile, porosity value of each sample (raw 84.55 %, flowrate 1L/sec 89.08%, temperature 30 ◦C 88.50 %).